Carbon dioxide — an active carrier of fumigants - Niamtsu, E. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The article discloses the possibility of reducing the rate of consumption of toxicological component in fumigant mixtures with the help of carbon dioxide in supercritical state, which performs technological functions concerning the rapid delivery of the poisonous part to the respiratory system of the pest. Characteristics of the supercritical state of carbon dioxide is given. Properties of supercritical fluid СО2 are shown. The problems that should be solved by lowering the rates of consumption of vaporous pesticides on the example of methyl bromide are identified.